Prayer and Mosque Attendance in Turkey (The Muslim world, 1928)
We are indebted to Mr. Ernest Pye, of the School of Religion, Athens, for the following extracts from the Turkish press. The editors of Resimli Ay made an investigation during the month of Ramadan (the Mohammedan month of fasting) regarding the present religious state of the people, especially as to their attitudes and relations with the mosques, and their comment was as follow.–Ed